THE ROLE OF INTERCULTURAL COMMUNICATION IN EFL CLASSES (Ustozlar uchun, 2025)
This article explores the significance of intercultural communication in English as a Foreign Language (EFL) classrooms. It examines how understanding cultural diversity enhances language learning and promotes mutual respect among learners from different backgrounds. The paper discusses the relationship between language and culture, methods of integrating intercultural competence into EFL teaching, and the challenges teachers face in fostering intercultural awareness. It also highlights practical strategies for developing students’ communication skills in multicultural contexts.